Original paperPrevalence of selected organ-specific autoantibodies in rheumatoid arthritis and primary Sjögren’s syndrome patients - Koszarny, Arkadiusz; Majdan, Maria; Dryglewska, Magdalena; Tabarkiewicz, Jacek (Reumatologia/Rheumatology, 2015)
Objectives : The aim of the study was to investigate the prevalence of selected organ-specific autoantibodies in rheumatoid arthritis (RA) and primary Sjögren’s syndrome (pSS) patients, and discuss their clinical significance. Material and methods : The study included 121 RA and 30 pSS patients. Sera were tested for the presence of autoantibodies to thyroid peroxidase (anti-TPO), thyroglobulin (anti-TG), TSH receptor (TRAbs), mitochondrial antigen M2 (AMA-M2-3E) and gliadin-analogous fusion peptides (anti-GAF(3X)) using the ELISA method. Non-organ-specific antibodies were determined: rheumatoid factor in IgM class, anti-citrullinated peptide antibodies and antinuclear antibodies. The occurrence of antibodies was also examined with regards to RA activity. Results : The following autoantibodies were detected in RA patients: anti-TPO – 13 (10.7%), anti-TG – 6 (5%), AMA-M2-3E – 3 (2.5%), anti-GAF(3X) – 5 (4.1%). The respective levels of these autoantibodies in pSS patients were 3 (10%), 2 (6.7%), 4 (13.3%) and 2 (6.7%). Polyautoimmunity was confirmed in 34 RA patients (including 20 cases of autoimmune thyroid disease [AITD]) and in 6 pSS patients (6 cases of AITD). When RA patients were divided into anti-TPO positive and anti-TPO negative groups, we found a statistically significant relationship between groups regarding age and hemoglobin concentration. In pSS patients the anti-TPO positive group was less likely to use immunosuppressive drugs as compared with the anti-TPO negative group. Anti-TPO was significantly more frequently detected in RA + AITD vs. RA, RA + SS + AITD vs. RA and in pSS + AITD vs. pSS patients. Conclusions : Organ-specific autoantibodies are relatively frequently observed in patients with RA and pSS. Their presence is connected with the clinical picture of the diseases.